Anthropometric indices, clinical symptoms and nutritional knowledge of adolescent girls of Vaniyambadi, Vellore District, Tamil nadu - M. ESWARI GOPI; ARUNA NARAYANAN (International Journal of Pharma and Bio Sciences, 2018)
Adolescent girls in India suffer from gross nutritional inadequacies however data on the nutritional profile of adolescents girls of Vaniyambadi are scanty. Hence this study aims to assess the current nutritional status of these girls, as this will help to plan an interventional program in future. Duration of the study was three months, in which survey method was implemented. Eight hundred adolescent girls (16 and 20 years) volunteered for the study. Anthropometric measurements, Clinical assessment, and nutrition education were done. SPSS (version 9) was used to analyze the data. The mean height, weight and body mass index of the selected girls ranged from 151.0±9.61 (16 years) to 153.2± 6.25cms (17 years), 43.6±6.87 (16years) to 46.9 ±7.72kg (20 years) and 19.02±1.31 (16 years) to 20.14 ±3.33 (20 years) respectively. Adolescents with BMI values of less than 18.5 were considered to be suffering from Chronic Energy Deficiency CED), while 61.8 percent of the participants of the current study could be categorized as normal and none of the respondents of the study were obese. The nutritional knowledge score of the selected adolescent girls improved at the end of the nutrition education programme. Most of the adolescent girls of the present investigation were undernourished.